Etika Pendidik Perspektif Imam Badruddin Ibnu Jama’ah dalam Kitab Tadzkiratus Sami’ Wal Mutakalim FiiAdabil ‘Alim Wal Muta’alim - Harahap, Ilham Adiansyah; Nahar, Syamsu; Hanum OK, Azizah (Kamaya: Jurnal Ilmu Agama, 2025)
This study on the ethics of educators from the perspective of Imam Badruddin Ibn Jama’ah in the book Tadzkiratus Sami’ Wal Mutdcakallim FiiAdabil ‘Alim wal Muta’aliman dits relevance to the code of ethics of teachers in Indonesia fills some gaps in previous studies. The purpose of this study is toanalyze the ethics of educators from the perspective of Imam Badruddin Ibn Jama’ah in his bookTadzkiratus Sami’ Wal Mutakallim FiiAdabil ‘Alim wal Muta’alim. This study uses a type of research with a library research approach (Library Research), which is included in the category of qualitative research. The ethics of a teacher according to Imam Badruddin Ibn Jama’ah emphasizes the importance of spiritual, moral, and scientific integrity. Teachers must have muroqobah (a sense of being watched by Allah), maintain the nobility of knowledge, beascetic to wards the world, and cleanse their intentions from world lyambitions. Educator ethics play an important role in the formation of educator character who not only teaches knowledge, butals of ormsthemorals and ethics of students. In Islamic thought, educator ethics have been discussed by many figures, one of whom is Imam Badruddin Ibn Jama’ah (1241-1333 AD). In his work Tazkirat as-Sami’ waal-Mutakallim fi Adab al-‘Alim waal-Muta’allim, Imam Ibn Jama’ah provide sguidance on the behavior and manners that must be possessed by an educator. Educator ethics according to Imam Badruddin Ibn Jama’ah in Tadzkiratus Sami’ wal Mutakallim are very relevant and in line with the Code of Ethics for Teachers in Indonesia. Values ​​such as maintaining dignity, being fair, being humble, having noble morals, professionalism, and spiritual awareness (muroqobah) are the common foundation in forming ideal educators—both morally, intellectually, and spiritually. These ethics not only streng then the quality of teachers personally and professionally, butal so encourage the creation of a civilized, conducive, and transformative learning atmosphere.